OZCEL (OZ CARE AND CLEAN) PENGEMBANGAN ALAT PEMBASMI HAMA MENGGUNAKAN OZONISASI SEBAGAI UPAYA PENGGANTI PESTISIDA PADA PERTANIAN - Awal Bahtera Suhiyar; Ligan Ayu Pamulang; Ari Prayogo (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractThe research objectives are to (1) design Ozcel(Oz Care and Clean) usingozonization (2) to find out how it works and (3) to reveal its performance as an effortto substitute pesticides. The type of the research is a development research. Theprocess of making Ozcel covers designing, preparing the equipment and materials,making the electronic circuit of PWM driver, making a box and lay out, assembling theparts of Ozcel, and testing the function of Ozcel as a pest eradicator. The result of theresearch is the design of Ozcel (Oz Care and Clean) consisting of importantcomponents, which among other things are a motorcycle coil as a high voltagegenerator functioning as ozone gas generator and PWM circuit as the driver of the coil.The dimension of Ozcel is 25 x 15 x 15 cm. Ozcel works as the high voltage of the coilis generated to produce electric plasma. The oxygen is then flown through the plasmaand the oxygen will react to become ozone or O3. Based on the analysis of itsperformance, Ozcel (Oz care and clean), is shown to have an effcet on preserving fruitsafter the harvest. Ozcel makes the fruits and vegetables remain fresh longer. In thisway the preserving process is carried out without using preservatives and isenvironment friendly.